Serangan Organisme Penganggu pada Pertanaman Hortikultura di Kabupaten Jambi - Dwi Lestari, Azzahra Nur; Arsi, Arsi; Dahlia, Sinta; br Sitepu, Cici Veronika; Rhamadani, Aulia; Damanik, Ester Elisia; Marchelia, Shela (Seminar Nasional Lahan Suboptimal, 2024)
Lestari, A. N. D., Arsi, A., Dahlia, S., Sitepu, C. V, Rhamadani, A., Damanik, E. E., & Marchelia, S. (2024). Attack of disruptive organisms on horticultural plantations in Jambi Regency. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-12 Tahun 2024, Palembang 21 Oktober 2024. (pp. 700–710).  Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Horticultural crops are an important component in agriculture that has several types such as the cultivation of vegetable crops, fruits, flower plants, and medicinal plants. One of the causes of low productivity of horticultural crops is due to the attack of plant pest organisms (OPT). To control the damage to the crops, farmers use synthetic pesticides. The aimed of study was carried out to identify insect pest species in horticultural crops in Paal Merah sub-district and Sungai Gelam sub-district, Jambi. The data obtained was using the purposive sampling method and 36 sample plants were taken using sampling intervals. The results obtained by some farmers aged 40-50 years with an average level of elementary education. Data from interviews with 10 farmers using pesticides and observation of the intensity of pest attacks was 23.47% and disease was 37.78%. Pests that attack horticulture are Liriomyza sp., Aulacophora indica, Spodoptera litura, Bactrocera sp., Rattus argentiventer., Sanurus indecora., and Tetranychus sp. Diseases that attack are leaf spot, anthracnose, fruit rot, and orange black spot.